2012
DOI: 10.1039/c2fd20036h
|View full text |Cite
|
Sign up to set email alerts
|

Soy milk oleosome behaviour at the air–water interface

Abstract: Soy milk is a highly stable emulsion mainly due to the presence of oleosomes, which are oil bodies and function as lipid storage organelles in plants, e.g., in seeds. Oleosomes are micelle-like structures with an outer phospholipid monolayer, an interior filled with triacylglycerides (TAGs), and oleosins anchored hairpin-like into the structure with their hydrophilic parts remaining outside the oleosomes, completely covering their surface (K. Hsieh and A. H. C. Huang, Plant Physiol., 2004, 136, 3427-3434). Ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…In detailed interfacial studies of purified soybean oleosomes on the air-water interface, it was suggested that rupture of all the oleosomes occurs and that their membrane fragments absorb on the interface. 26 In another research where the behaviour of pure soybean oleosomes was studied on the O/W interface, the same explanation was suggested for the stabilization of the interface. 16 In both studies, it is supported that the oleosomes initially absorb intact on the interface and subsequently disintegrate into interfacially active membrane fragments.…”
Section: Oleosomes At the O/w Interfacementioning
confidence: 78%
“…In detailed interfacial studies of purified soybean oleosomes on the air-water interface, it was suggested that rupture of all the oleosomes occurs and that their membrane fragments absorb on the interface. 26 In another research where the behaviour of pure soybean oleosomes was studied on the O/W interface, the same explanation was suggested for the stabilization of the interface. 16 In both studies, it is supported that the oleosomes initially absorb intact on the interface and subsequently disintegrate into interfacially active membrane fragments.…”
Section: Oleosomes At the O/w Interfacementioning
confidence: 78%
“…Oil consists of approximately 88.1% triglycerides, 9.8% phospholipids, 1.6% unsaponifiable components and 0.5% free fatty acids (Salunkhe et al, 1992). The majority of oil is located in oil bodies (oleosomes) within the cotyledon cells (Waschatko et al, 2012). Oil bodies are found within the cytoplasmic network of the cells and are stabilised by small molecular weight proteins termed oleosins (Rosenthal et al, 1998), which make them more hydrophilic and easy to extract aqueously.…”
Section: Soybean Oilmentioning
confidence: 99%
“…Generally, commercial soy milk has dispersion stability attributable to the presence of oleosomes or forming aggregate formation of soy proteins on it [28,29]. Therefore, no precipitate is produced from commercial soybean milk by low centrifugal gravity as 400×g.…”
Section: Purification Of the Protease As A Soybean Milk Curdling Enzymementioning
confidence: 99%